Application of thermoelectric devices in performance optimization of a domestic PEMFC-based CHP system. (15th August 2021) - Zou, Wen-Jiang; Shen, Kun-Yang; Jung, Seunghun; Kim, Young-Bae
Abstract: Polymer electrolyte membrane fuel cell (PEMFC)-based combined heat and power (CHP) hybrid system is a promising power source to achieve residential energy independence because it can generate electricity and heat simultaneously. However, a large amount of energy waste remains because the ratio of electricity and heat output fluctuates with the end user requirement. A thermoelectric generator (TEG) is introduced to enhance the power output of the PEMFC-CHP hybrid system. It can also increase system performance and alleviate the mismatch between energy supply and demand. This research establishes a comprehensive model of the PEMFC-TEG-CHP hybrid system to deeply analyze its operating mechanism and optimize power output performance. The corresponding experimental setup is built to validate its availability of the proposed model. Results reveal that the conversion efficiency of TEG is 0.408% when converting heat to electric power from a 5 kW PEMFC-based CHP hybrid system. Furthermore, the total hybrid system efficiency can reach 85.1% with increments in the electrical efficiency and the energy efficiency of the CHP system of 0.325% and 0.129%, respectively, by exploiting 30-unit TEG modules. The present study demonstrates the feasibility of the PEMFC-TEG-CHP system and implies the promising future of low-grade heat energy recovery using TEGs. Highlights: PEMFC-based combined heat and power hybrid system is developed. A thermoelectric generator is introduced to enhance the power output of the PEMFC-CHP. Experimental results prove high efficiency of the PEMFC-TEG-CHP hybrid system.